The Use of Personal Deiksis In Expressing The Meaning of The Short "In The Body Of Tarra In The Word Of The Tree" By Faisal Oddang: A Stilistic Overview - Nursa'adah, St.; Bandung, AB Takko; Nurhayati, Nurhayati (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2025)
The purpose of this study is to reveal the types of deixis and the function of deixis in uncovering the meaning of the short story " Di Tubuh Tarra dalam Rahim Pohon ". This research uses stylistic theory. Stylistics examines the use of language in a literary work and the effectiveness of its use. This stylistic study can move at the pragmatic level. This type of research is qualitative research. The method used in this research is descriptive analytical method. The results of the study show that the types of deixis in the short story include first-person deixis with the word I as many as 13 and I as many as 8, the use of the second person with the word you as much as 37 and the second plural with the word we as much as 5. The third persona he as many as 9, he as much as 3. The third plural with the word we as many as 6 and they are 6. The use of the first persona deixis is dominantly used in the short story. Through the use of persona deixis, it is found the meaning of the social stratification of the Toraja people in the short story " Di Tubuh Tarra dalam Rahim Pohon "